{Laser treatment for the management of genitourinary syndrome of menopause after breast cancer. Hope or hype?} - Tranoulis, A.; Georgiou, D.; Michala, L. (International Urogynecology Journal, 2019)
© 2019, The International Urogynecological Association. Introduction and hypothesis: Fractional CO2 and vaginal erbium lasers have emerged as potential treatment options for genitourinary syndrome of menopause (GSM) in breast cancer (BC) survivors. Methods: We conducted a systematic review of the literature to ascertain whether available evidence supports the efficacy and safety of laser treatment for GSM in BC patients. MEDLINE, Scopus and Cochrane Library databases were systematically searched from inception until March 2019 for studies on laser treatment for GSM in BC patients. Results: We yielded six observational studies meeting the inclusion criteria. The studies were of moderate quality. Taken together, the studies suggest that laser treatment may significantly alleviate or resolve the GSM-related symptoms and improve sexual function. Furthermore, a significant increase of the vaginal health index was reported. Positive effect was maintained up to 12 months. The safety and tolerability profile is encouraging, given that no adverse effects were reported, while only few patients discontinued laser treatment, owing to reported discomfort. Conclusions: Our findings suggest that lasers appear to be effective and practical treatment options in BC survivors suffering from GSM. Evidence concerning long-term effects is lacking. The rationale for repeated treatment remains uncertain. Randomized controlled trials that collate different frequencies, intensities and durations are warranted to ascertain a dose-response relationship and adherence.
Keywords: breast cancer; Genitourinary syndrome of menopause; Laser; Vaginal atrophy